Thermal Stabilization of Permafrost Using Thermal Coils Inside Foundation Piles - Alexander Lavrik; George Buslaev; Mikhail Dvoinikov (Salehan Institute of Higher Education, 2023)
The article deals with the issue of thermal stabilization of soils to preserve the stability of pile foundations in permafrost conditions. The purpose of the work is to develop a technology for year-round freezing of soils by supplying coolant cooled by a refrigeration machine to thermal elements placed inside piles. In this work, the temperature regime of the system